DAMPAK INFRASTRUKTUR DIGITAL TERHADAP MOBILITAS KOTA BANDARLAMPUNG - Dwi Wulandari; Muhammad Zainal Ibad; Goldie Melinda Wijayanti (Jurnal Perencanaan dan Pengembangan Kebijakan, 2022)
Lampung Province, especially in Bandarlampung City, according to the spatial plan (RTRW), Lampung Province has been designated as one of the National Activity Centers (PKN) and as a strategic area for Sumatra Island in the transportation sector. This condition encourages Bandarlampung City to apply the Smart City concept in developing its city, in realizing this concept Bandarlampung City utilizes digital infrastructure platforms in its activities. The digital infrastructure platform is expected to be a solution to push Bandarlampung City towards the realization of the Smart City concept and improve the public's mindset towards technological advances to facilitate and improve the quality of public services. In addition, according to Castells (2010) theory, the existence of this digital platform will reduce mobility in Bandarlampung City because many public service activities are carried out from home without transportation. The digital infrastructure platform of Bandarlampung City that include in this research is a platform for local transportation network infrastructure, government, education, health, trade and commerce, clean water and electricity networks and telephone network utilities. In this research, it was identified that there was a connection between changes in the frequency of use of digital infrastructure platforms which in fact affected the mobility of the citozens of Bandarlampung City.